PENGARUH TEKNOLOGI INFORMASI, INTENSITAS KOMPETISI PASAR, STRATEGI BISNIS DAN INFORMASI SISTEM AKUNTANSI MANAJEMEN PADA KINERJA PERUSAHAAN (Studi pada perusahaan manufaktur di kawasan industri modern Cikande Kabupaten Serang – Banten) - Firdaus, Dodi; Yazid, Helmi (Pascasarjana Universitas Sultan Ageng Tirtayas, 2017)
This study aims to examine the relationship between information technology, the intensity of market competition and business strategy on company performance with management accounting system as intervening variable. The population in this research is manufacturing company that exist in Modern Industrial Estate Cikande. The method used is descriptive method with saturated sampling technique. With analytics units are financial division managers, marketing division managers, HR division managers and production division managers. The data in this study were obtained by distributing questionnaires directly to respondents, 144 distributed questionnaires correspondents and only 59 returned questionnaires. The data in this research is analyzed by strcutural equation modeling (SEM) method, with Partial Least Square (PLS) approach. The results of this study indicate that (1) Changes in business strategy due to changes in the intensity of competition causes a change in strategy, and this results in a change in MAS, thus affecting performance improvement directly and indirectly. (2) The development of information technology affect the management accounting system as the producer of information in the framework of planning, controlling and management decision making that impact on the improvement of performance directly and indirectly. (3) Changes in the intensity of competition affect the company's performance through MAS.Keywords: information technology, intensity of competition, business strategy, management accounting system (MAS), company performance, manufacturing company.